IMPLEMENTASI METODE SIMPLE ADDITIVE WEIGHTING (SAW) DALAM SISTEM INFORMASI LOWONGAN KERJA BERBASIS WEB UNTUK REKOMENDASI PENCARI KERJA TERBAIK - Darmastuti, Destriyana (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
Information systems existing vacancies still using a search based on attributes of eachrequest and there is no profile of a dataprocessing job providers and job seekers. Thiswill make it difficult for providers to screenprospective job applicants who have applied.This study aims to produce an informationsystem web based job which will bring togetherjob seekers and job providers and implementSAW method which can give job seekers the bestrecommendation according to criteria specifiedby the job provider. Web-based application builtusing PHP programming language and MySQLdatabase. The method used is Simple AdditiveWeighting Method (SAW). The criteria used isthe CPI score, height, marital status, age, highschools score, education level, accrediteduniversity, department accreditation,accreditation courses, eye conditions,experience, fitness courses and foreign languageskills (grades TOEFL). The results show that themethod Simple Additive Weighting (SAW) isable to produce job seekers the bestrecommendation based on the criteria required